2021
DOI: 10.3390/v14010025
|View full text |Cite
|
Sign up to set email alerts
|

Pandemics of the 21st Century: The Risk Factor for Obese People

Abstract: The number of obese adults and children is increasing worldwide, with obesity now being a global epidemic. Around 2.8 million people die annually from clinical overweight or obesity. Obesity is associated with numerous comorbid conditions including hypertension, cardiovascular disease, type 2 diabetes, hypercholesterolemia, hypertriglyceridemia, nonalcoholic fatty liver disease, and cancer, and even the development of severe disease after infection with viruses. Over the past twenty years, a number of new viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 142 publications
0
15
0
Order By: Relevance
“…Obesity is associated with unemployment, social disadvantages, and reduced socioeconomic productivity, thus increasingly creating an economic burden [3]. Furthermore, obesity has been shown to play an important role in the pathophysiology of numerous chronic diseases which include cardiovascular disease (CVD), dyslipidemias, type 2 diabetes (T2D), and cancer [4][5][6]. The fifth risk for attributable deaths in females was high body mass index (hBMI), while for the males, hBMI accounts for the sixth risk attributed to death in 2019 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is associated with unemployment, social disadvantages, and reduced socioeconomic productivity, thus increasingly creating an economic burden [3]. Furthermore, obesity has been shown to play an important role in the pathophysiology of numerous chronic diseases which include cardiovascular disease (CVD), dyslipidemias, type 2 diabetes (T2D), and cancer [4][5][6]. The fifth risk for attributable deaths in females was high body mass index (hBMI), while for the males, hBMI accounts for the sixth risk attributed to death in 2019 [7].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the result of a review of 70 published studies that showed a reduction in weight, body mass and fat percentage in fasted people with obesity ( 8 ). Previous reports showed that weight loss during RIF was due to the reduced food intake ( 2 ). Therefore, this could, in part, explain the observed weight loss in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Obesity has become a global public health issue with almost two billion individuals were overweight ( 1 ). Obesity is a global epidemic in developed countries and is associated with several comorbidities such as cardiovascular disease, type 2 diabetes and cancer ( 2 , 3 ). It has been reported that more than one-third of children and adolescents are with obesity ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Humanity has survived many severe pandemics previously [12][13][14]. In the last four decades, humankind has faced several deadly viral outbreaks, such as human immunodeficiency virus (HIV), severe acute respiratory syndrome coronavirus (SARS-CoV), H1N1 influenza virus, Middle East respiratory syndrome coronavirus (MERS-CoV), Ebola, and severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) [12,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%